Pemberdayaan Ekonomi Masyarakat Di Dukuh Kenaruhan Melalui Diversifikasi Produk Olahan Cabai - Jatmiko, Bayu; Juanita, Athifah; Tetuko, Muhammad; Azhari, Zakia Ilham; Lukmana, Muhammad Alfi; Gustafarin, Fachriansyah Panji; Sekartadji, Shafira Ayu; Gayatri, Muthia Sayyida; Satusani, Anis; Siregar, Ega Mawarni; Azmawati, Dian (Universitas Muhammadiyah Yogyakarta, 2025)
Dependence on the sale of fresh chili peppers has led farmers to face significant price fluctuations, particularly during the harvest season when prices tend to drop. The lack of innovation in agricultural product processing results in the low market value of chili peppers, which fails to provide maximum profit for farmers. Therefore, this community service program aims to address these issues through product diversification innovation, focusing on the production of chili oil. The methods implemented in this activity include socialization and direct assistance to the local community, particularly farmer groups and the PKK (Empowering Family Welfare) women’s groups. Socialization is conducted to provide an understanding of the benefits of product diversification as an effort to increase the added value of agricultural products, as well as digital marketing strategies that can expand market reach. Meanwhile, direct assistance includes technical training on selecting quality raw materials, hygienic processing techniques in compliance with food safety standards, and attractive, durable product packaging. The outcomes of this activity show an increased understanding among the community regarding chili processing innovation and the potential for agricultural-based business development. Some participants even expressed interest in independently developing chili oil-based businesses. Although there were some technical challenges during the implementation, such as power outages that hindered practical sessions and limited production equipment, alternative solutions were applied, such as the use of manual tools and additional training sessions, ensuring the smooth running of the entire program. The expectation for the future is that this innovation will provide long-term benefits for the welfare of the Kenaruhan village community by creating a more sustainable, independent agricultural ecosystem based on entrepreneurship. Furthermore, this program can serve as an inspiration for other regions to develop product diversification strategies as a solution to the price fluctuations of agricultural products